Hyperbaric oxygenation as a complementary process in the regeneration of skin in thermal burn using hyperoxia with vasoconstriction. - Rivadeneira, Jorge-Elías; Buitrón-Jácome, Pablo; Meneses-Salazar, Elmer; Yandún-Yalamá, Vicente; López Castillo, Andrea Poleth (Revista Ecos de la Academia, 2023)
Hyperbaric Oxygen Therapy (HBO) maintains elevated oxygen in tissues and muscle for more than four hours, increasing oxygen tension in body fluids; improving microcirculation, phagocytic activity of white blood cells; decreasing platelet aggregation, cardiac overload; it is bacteriostatic, bactericidal and antifungal, among other actions. The Patient has been admitted to Hyperbaric Oxygenation Treatment to treat thermal burn in 70% of the chest caused by boiling water with 1st and 2nd degree burns in a person. The aim of the research was to heal the thermal burn wound using hyperoxia with vasoconstriction. The type of research was experimental, with Preexperimental design. The research approach used was mixed, since 6 sessions were performed in hyperbaric chamber combining topical products and dressings in a patient; the techniques used are: observation and interview; instruments: hyperbaric chamber, oximeter and clinical history. Hyperoxia with vasoconstriction and Robin Hood effect is achieved in the six-week period, accelerating the speed of healing of the dermal tissue. HBOT accelerates healing and proliferation of regenerating cells of epidermal tissues with thermal burns.
Keywords: Hyperbaric oxygenation, healing, revitalization, ischemia, hypoxia, thermal burn.